BESARNYA PENGARUH PENERAPAN GAYA KEPEMIMPINAN PARTISIPATIF KOMANDAN SATUAN MILITER TERHADAP PROFESIONALISME PRAJURIT - Dedy Ary Yuanto; Sudardi Sudardi; Firdaus Firdaus (Jurusan Manajemen Fakultas Ekonomi Universitas Sriwijaya, 2019)
This research aims to determine how much the influence of leadership style of Military Commander Unit on complex situation in order to accomplish their duties.In Participate leadership, the leader should work together with their subordinates to solved the organization problems. The method in this research is the quantitative method. First of all, Validation and reliability test were finished then the questionnaire delivered to 86 samples from 110 populations that already decided. Then, data analysis with normality test, variant homogeneity test and anova test with SPSS version 25. For the research hypotheses test the participate leadership style (X) on soldier professionalism (Y), the result of the significant point from the simple regression is 0,002 point, smaller then probability 0,05 point, for the conclusion there were significant influence on variable (X) to Variable (Y). R-square is 0,642, it means there is influence on leadership style (X) to variable (Y) amount 64,2 %, on the other hand 35,8 % are influence by no research variable.